The Impact of Using Quizizz Paper Mode on Results Study Student and The realization of Sustainable Development Goals (SDGs) in Elementary School - Munofa Khoeron Rizoq; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
Research this aim for analyze influence use Quizizz paper mode to results Study students and their contributions in realize objective Sustainable Development Goals (SDGs) in elememtary schools. background research this is still low utilization technology in the learning process and its limitations access digital devices for student school basic research This use approach quantitative with quasi-experimental design (posttest only control group design). The sample consisted of from students in the Gugus Ramayana, Kubangkangkung, Cilacap, which is divided in two groups: experimental ( using Quizizz paper mode ) and control ( learning conventional ). Data collected through test results study and analyze using the t-test. Research results show that use Quizizz paper mode give influence positive to improvement results Study students (t = 3.489; p < 0.05). In addition, the learning model this also supports achievement SDGs indicator 4.1 ( Asymp Sig. = 0.000 < 0.05), namely ensure education quality and inclusive foundation. Quizizz paper mode become solution learning based adaptive technology to limitations digital means, as well as push learning interactive and fun. Findings This confirm importance innovation technology simple in support quality education base especially in areas with limitations digital access.